Human Microglia Extensively Reconstitute in Humanized-BLT Mice With Human Interleukin-34 Transgene and Support HIV-1 Brain Infection - Zhang, Jianshui; Lohani, Saroj Chandra; Cheng, Yilun; Wang, Tao; Guo, Lili; Kim, Woong-Ki; Gorantla, Santhi; Li, Qingsheng (Frontiers in Immunology, 2021)
Humanized bone marrow-liver-thymic (hu-BLT) mice develop a functional immune system in periphery but have a limited reconstitution of human myeloid cells, especially microglia, in CNS. Further, whether bone marrow derived hematopoietic stem and progenitor cells (HSPCs) can enter the brain and differentiate into microglia in adults remains controversial. To close these gaps, in this study we unambiguously demonstrated that human microglia in CNS were extensively reconstituted in adult NOG mice with human interleukin-34 transgene (hIL34 Tg) from circulating CD34+ HSPCs but no in hu-BLT NOG mice, providing strong evidence that human CD34+ HSPCs can enter adult brain and differentiate into microglia in CNS in the presence of hIL34. Further, the human microglia in the CNS of hu-BLT-hIL34 NOG mice robustly supported HIV-1 infection reinforcing the notion that microglia are the most important target cells of HIV-1 in CNS and demonstrating its great potential as an in vivo model for studying HIV-1 pathogenesis and evaluating curative therapeutics in both periphery and CNS compartments.